Topografías variables del poder: las relaciones entre movimientos sociales y el Estado argentino en dos tiempos - Virginia Manzano (Amnis)
Over the 1990s, Latin America became a privileged scenario for both the implementation of neoliberal policies and the emergence of intense social protests that challenged those programs of structural adjustment and austerity. Those mobilizations reconfigured forms of government and, in the cases of Ecuador and Bolivia, partially refunded the basis of the modern liberal State through the endorsement of notions such as those of multi-nationality and « good living/to live well ». In that framework, this article studies the relational character of the State and social movements in Argentina by looking at the historical articulation of neoliberal forms of government and the shaping of a favorable context for the implementation of popular politics of income distribution. From an ethnographic perspective, the article analyzes the making of the unemployed people’s movement (piquetero) in La Matanza District (Buenos Aires) and the Tupac Amaru Movement in Jujuy province, in order to account for variable topographies of power.